The Effect of Small-Sided Games Training on Futsal Passing and Dribbling - Didik Purwanto; Andi Saparia; Rahma; Andi Sultan Brilin Susandi Eka Wahyudhi (Tadulako Journal Sport Sciences And Physical Education, 2026)
Performance in competitive futsal relies heavily on mastery of technical skills, particularly passing and dribbling. However, conventional training techniques often fail to replicate the high-pressure dynamics of real matches, particularly in elementary-level development programs with limited training opportunities. Objective: This study evaluated the effectiveness of a Small-Sided Games (SSG) training intervention on the passing and dribbling abilities of adolescent futsal players. This study used a quasi-experimental design with 15 extracurricular students at MAN 2 Palu who were assigned to a pre-test and a post-test. The intervention consisted of eight weeks of SSG training in 3v3 and 4v4 formats, with a focus on controlling space constraints and quick transitions. Technical skills were measured using standardized tools for passing and dribbling in futsal. SPSS 26 was used to analyze the data using a paired t-test, also known as a paired samples t-test. Results showed a highly significant improvement in technical performance (t = 16.733, p < 0.001). The mean technical score increased by 61.6%, rising from 4.33 ± 0.82 to 7.00 ± 0.91. Strong intervention reliability across the sample was confirmed by a 95% confidence interval (CI: 2.325–16.733). The use of Small-Sided Games (SSG) led to a significant increase in ball contact frequency and in decision-making under time-space pressure. According to this study, Small-Sided Games (SSG) are the most time-efficient and effective pedagogical tool for improving technical skills in school-based sports programs. These results enable coaches to shift from linear, repetitive drills to a non-linear, game-based training approach.